(untitled) (Texas Journal of Multidisciplinary Studies, 2024)
This scientific article discusses the concept of operational-search and forensic characteristics of crimes and its essence, the importance of operational-search and forensic characteristics of crimes in solving crimes, as well as scientific approaches to the operational-search and forensic characteristics of crimes in the customs sphere in the Republic of Uzbekistan, explains the opinions of scientists and their comments